Climate Change and Food Security in South Asia - Lal, Rattan; Sivakumar, Mannava V.K.; Faiz, S.M.A.; Mustafizur Rahman, A.H.M.; Islam, Khandakar R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
This book addresses an important topic of food security in South Asia with specific reference to climate change. Of the 1 billion food insecure people in the world, more than 30% are in South Asia. The problem of food insecurity may be exacerbated by the projected climate change especially because of the water scarcity caused by rapid melting of the glaciers in the Himalayas and increase in variability in monsoonal rains and frequency of extreme events. Furthermore, large populations of Bangladesh and other coastal regions may be displaced by sea level rise. Thus, this volume addresses recommended land use and soil/water/crop/vegetation management practices which would enable land managers to adapt to climate disruption by enhancing soil/ecosystem/social resilience. In addition to biophysical factors, this book also addresses the issues related to human dimensions including social, ethnical and political considerations.
Keywords: Environmental sciences; Forests and forestry; Plant breeding; Climatic changes; Soil conservation; Sustainable development; Environment; Soil Science & Conservation; Climate Change; Plant Genetics & Genomics; Forestry Management; Sustainable Development